Kinerja Guru Sekolah Dasar di Masa Pandemi Covid19 di Kota Manado - Margareta O Sumilat; Sarah Tombokan (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to determine whether the performance of elementary school teachers in Manado City was in accordance with the expectations of the parents. To answer the objectives of this study, researchers conducted research based on the quantitative descriptive method with Importantnce Performance Analysis (IPA) method analysis. The results of the research conducted show that based on the results of the calculation of the average performance appraisal (performance) performance of elementary school teachers in Manado City is below the average rating of expectations (Importance): 2.67 <4.21 and the performance of each variable of service quality. The results of the respondent's assessment score (suitability level) are below 100% (65.7% <100%) which means that it is not satisfactory. The interpretation of the Cartesian diagram can be explained as follows: aspects or attributes that affect teacher performance satisfaction, namely aspects of work quality (1) and aspects of communication. Otherwise. Aspects that are good and in accordance with what the community expects and their performance needs to be maintained (quadrant B) and the result is only one indicator, namely ability (4). In other words, there are achievements made by teachers, in this case, according to the parents, is the teacher's ability to carry out teaching. From the results of the research and data analysis, it can be concluded that based on the analysis of the results of the study, it can be concluded that the overall indicator of the performance level of teachers in elementary schools in Manado City based on processing and data analysis falls into the Low category which must be improved implementation.